Applications of N,N-bis(phosphonomethyl)glycine-derived Sn4+ or Co2+ phosphonates as proton conductors or energy-conversion electrocatalysts. - Cañamero-Cebrián, Fernando; Pérez-Colodrero, Rosario Mercedes; Vílchez-Cózar, Álvaro; Bazaga-García, Montse; Ramírez-Losilla, Enrique; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio (My University, 2023)
Metal phosphonates (MPs), a subclass of coordination polymers, may exhibit acidic groups such as POH, SO3H, COOH, N+-H, etc. Combining these features with electrocatalytically active transition metals, make them highly appealing in the field of fuel cells and electrolysers, as potential proton conductors and/or precursors of electrocatalysts [1,2]. Herein, we investigate the synthesis, characterization and applications of a series of Co2+ and Sn4+ phosphonates derived from glycine-N,N-bis(methylenenphosphonic acid) (BPMGLY). In the case of the tin derivative, an amorphous compound, Sn(C4H11O8NP2)0.75Cl2.5(H2O)2.5 (Sn4+- BPMGLY), was obtained by hydrothermal synthesis. Its pyrolytic treatment at 700 ºC in air led to an amorphous pyrophosphate, (Sn4+- BPMGLY@700). Regarding cobalt phosphonates, three crystalline phases with composition [Co(C4H9O8NP2(H2O)2]·nH2O (n=0, 2) were obtained and their crystal structure were solved. All families were extensively studied as proton conductors across a wide range of temperature and humidity conditions, displaying the Sn4+ derivatives the highest conductivity values of 7.99·10-4 and 6.63·10-3 S·cm-1 for Sn4+-BPMGLY and Sn4+-BPMGLY@700, respectively, at 95 °C and 95% relative humidity (RH) (Figure 1a). Furthermore, the cobalt phosphonates were utilized as precursors for non-precious metal catalysts (NPMCs), by pyrolysis in 5%-H2/Ar at different temperatures and studied as electrocatalysts towards the oxygen evolution reaction (OER), hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR)
Keywords: Química inorgánica; Fósforo - Compuestos; Catalizadores metálicos; Metal Phosphonates; HER; OER; ORR; Electrocatalysts; Structure-properties correlations; Proton conductivity